Magnetoencephalography with optically pumped magnetometers (OPM-MEG): the next generation of functional neuroimaging - Brookes, Matthew J.; Leggett, James; Rea, Molly; Hill, Ryan M.; Holmes, Niall; Boto, Elena; Bowtell, Richard (Trends in neurosciences (Regular ed.), 2022)
Magnetoencephalography (MEG) measures human brain function via assessment of the magnetic fields generated by electrical activity in neurons. Despite providing high-quality spatiotemporal maps of electrophysiological activity, current MEG instrumentation is limited by cumbersome field sensing technologies, resulting in major barriers to utility. Here, we review a new generation of MEG technology that is beginning to lift many of these barriers. By exploiting quantum sensors, known as optically pumped magnetometers (OPMs), ‘OPM-MEG’ has the potential to dramatically outperform the current state of the art, promising enhanced data quality (better sensitivity and spatial resolution), adaptability to any head size/shape (from babies to adults), motion robustness (participants can move freely during scanning), and a less complex imaging platform (without reliance on cryogenics). We discuss the current state of this emerging technique and describe its far-reaching implications for neuroscience. Magnetoencephalography (MEG) allows noninvasive electrophysiological imaging of human brain activity. However, current MEG technology has significant limitations.Optically pumped magnetometers (OPM)-MEG is a new type of MEG instrumentation, promising several advantages compared with conventional scanners: higher signal sensitivity, better spatial resolution, more uniform coverage, lifespan compliance, free movement of participants during scanning, and lower system complexity.We describe the principles underlying OPM-MEG and its components, including noncryogenic field sensors and magnetic shielding technologies.We discuss how the OPM-MEG technology is impacting neuroscience, enabling researchers to overcome limitations of conventional human imaging techniques and tackle new types of research questions.